Reduction of Cirsium fangii (Asteraceae, Cardueae) to the synonymy of C. leo and description of a new species, C. sichuanense, from Sichuan, China - Jin, Zi-Chao; Chen, You-Sheng (Phytotaxa, 2022)
Based on critical observations on herbarium specimens (including type material) and living plants in the wild, we demonstrate that Cirsium fangii (Asteraceae, Cardueae) is a synonym of C. chienii and both should be placed in the synonymy with C. leo. Moreover, we found that most of the specimens previously identified as C. fangii from Sichuan are different from its type material by an array of characters and represent a new species. We name the new species as C. sichuanense and describe it herein.